2003
DOI: 10.3168/jds.s0022-0302(03)73621-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fermentation and In Vitro Digestion on the Formation of Angiotensin-I-Converting Enzyme Inhibitory Activity from Pea and Whey Protein

Abstract: Pea and whey protein were fermented by Lactobacillus helveticus and Saccharomyces cerevisiae in monoculture and in combination at 28 and 37 degrees C in order to release angiotensin-I-converting enzyme (ACE) inhibitory peptides. The fermentation products were subjected to in vitro gastrointestinal digestion, and the digests of nonfermented samples served as controls. After fermentation, the ACE inhibitory activity (%) increased by 18 to 30% for all treatments, except for the fermentations of whey protein with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 31 publications
8
85
1
3
Order By: Relevance
“…In addition, 15 min heat treatment effectively increased the ACE-inhibitory activity of the stomach digest [43,131]. Digestion simulating the physiological conditions of pea proteins sufficed to achieve the highest ACE-inhibitory activity with IC50 value of 0.076 mg/ml [132]. Furthermore, it has been suggested that red lentil protein hydrolysates have ACE-inhibitory properties.…”
Section: Legume Derived Peptidesmentioning
confidence: 96%
“…In addition, 15 min heat treatment effectively increased the ACE-inhibitory activity of the stomach digest [43,131]. Digestion simulating the physiological conditions of pea proteins sufficed to achieve the highest ACE-inhibitory activity with IC50 value of 0.076 mg/ml [132]. Furthermore, it has been suggested that red lentil protein hydrolysates have ACE-inhibitory properties.…”
Section: Legume Derived Peptidesmentioning
confidence: 96%
“…Several studies have accordingly provided evidence for this realization -as happened with Manchego cheese, as well as with other fermented solutions and infant formulae [100,261,[278][279][280][281]; for instance, a potent antihypertensive peptide was released via gastrointestinal digestion from a precursor with poor ACE-inhibitory activity in vitro [282] -and some peptides possess a remarkable intrinsic stability, whereas others are susceptible to unwanted degradation [136,261,281]; however, whether of any of those options will apply cannot be known in advance.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…One example is YP, the IC50 of which is 720 M; however, it significantly decreases blood pressure between 2 and 8 h after oral administration to SHR [283]. It should be emphasized that in vivo tests of (putatively) promising bioactive peptides should not come into play before careful in vitro models have been checked -as they can provide useful preliminary information on the stability of such peptides upon exposure to the various peptidases and proteinases that they will likely find in the gastrointestinal tract, prior to eventual transport across the intestinal barrier [278][279].…”
Section: Bioavailabilitymentioning
confidence: 99%
See 2 more Smart Citations